ДЕОНТОЛОГІЧНИЙ СКЛАДНИК ОЦІНЮВАЛЬНО-АНАЛІТИЧНОЇ КОМПЕТЕНТНІСТІ ПЕДАГОГА - Smagina , Taisa (Науковий вісник Ужгородського університету. Серія: «Педагогіка. Соціальна робота», 2025)
Із затвердженням професійного стандарту вчителя виникла необхідність в якісно іншій підготовці педагога, що дає змогу поєднувати фундаментальність професійних базових знань з інноваційністю мислення і практико-орієнтованим дослідним підходом до реалізації нового формату оцінювання. Аналіз професійного стандарту вчителя спонукає до більш детального визначення й осмислення ціннісної сфери професійної діяльності педагога. Саме тут, на нашу думку, мають бути використані здобутки відносно нової сфери наукового знання – педагогічної деонтології. Метою статті є виявлення і визначення місця деонтологічного складника в межах оцінювально-аналітичної компетентності педагога за формулюванням професійного стандарту вчителя. На основі порівняльного аналізу літературних джерел сформульовано авторські висновки. Мотиваційно-ціннісний (особистісний) компонент структури оцінювально-аналітичної компетентності яскраво виявляє особистісні риси педагога, що дає можливість розкрити мотиви і прагнення учнів. Це дає підставу визначити мотиваційно-ціннісний (особистісний) компонент як деонтологічний складник оцінювально-аналітичної компетентності педагога. Він має стати спусковим механізмом справедливого та мотивувального оцінювання, що дасть змогу учневі/-ці відчути себе цінним/-ою і знаходити сенс у навчанні. Педагог формує у себе певні моделі професійної поведінки, які є виявленням сформованості його оцінювально-аналітичної компетентності. With the approval of teachers’ professional standard there is a need for a qualitatively different teacher training, which allows to combine the fundamentals of professional basic knowledge with innovative thinking and practice-oriented research approach to the implementation of a new evaluation format. Modernization of the system of education in Ukraine has radically changed the «portrait» of the modern teacher and the requirements for his work. There is a demand for professionals who not only know their subject well, but also have a flexible professional self-awareness, emotional intelligence and communication skills focused on creativity, innovation, entrepreneurship. There is a need to create a route map for the development of teachers` professionalism in Ukraine. The analysis of the teacher’s professional standard encourages to more detailed definition and comprehension of the value sphere of teacher`s professional activity. It is here, in our opinion, that the achievements of a relatively new field of scientific knowledge − pedagogical deontology − should be used. The purpose of the article is to identify and determine the place of the deontological component within the teacher`s evaluative-analytical competence in the formulation of teacher`s professional standard. Based on the comparative analysis of literature sources, the author's conclusions are formulated. Motivational-value (personal) component of the structure of evaluative-analytical competence clearly reveals the personal traits of the teacher, which gives the opportunity to reveal students` motives and aspirations. This gives grounds to define the motivational-value (personal) component as a deontological component of the teacher’s evaluative-analytical competence. It should be a trigger for fair and motivating assessment that enables the student to feel valued and find meaning in learning. The teacher forms certain models of professional behavior, which are a manifestation of the formation of his evaluative-analytical competence.